Awareness Of Oral Health In Students Of Medicine And Dental Medicine - Damayanti, Rindu; Anugrah, Aditya; R, Patricia Widyanandana; M, Jasmine Azahra; L, Defita Ayu (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: To examine the different levels of awareness about oral health in the third semester students of Faculty of Medicine and Faculty of Dental Medicine Universitas Airlangga. Method: The research design used was descriptive research with survey data collection methods in the online form using google form. Data analysis was performed using the chi square method to get results. Results: Based on research that has been done, Faculty of Medicine students have a percentage level of awareness (understanding) about oral health with a category of understanding as much as 76% while Faculty of Dental Medicine students have a percentage of level of awareness (understanding) about oral health as much as 100%. Conclusion: There is no significant difference in the level of awareness (understanding) about oral health in Faculty Of Medicine and faculty of dental medicine students at Universitas Airlangga.